Comparative analysis of the level's aggression of women and men training Brazilian Jiu - Jitsu in the light of the possibilities for therapeutic purposes - Marta Wojdat; Roman Ossowski (Kazimierz Wielki University, 2019)
Aim: Compare the level of aggression of women and men training Brazilian Jiu-Jitsu (BJJ) with average aggression from a randomly selected control group and analyze the results in terms of therapeutic value. Material and methods: A group of 38 women and a group of 43 men practicing Brazilian Jiu-Jitsu were examined using the questionnaire to determine the level of aggression "Aggression Questionnaire" by Buss, Perry, the "Amity" Institute in the Polish adaptation. The collected data was compared with the results of women (35 people) and men (40 people) from the control group. Results: Lower levels of total aggression were observed among women and men training Brazilian Jiu-Jitsu relative to the control group. There was also a lower level of aggression in the group of women than in the group of men, and a decrease in the level of total aggression along with the increase in the training experience. Conclusions: The long-term training of Brazilian Jiu-Jitsu reduces the level of aggression. Training this sport can be one of the ways to reduce the level of aggression. Psychologists may recommend the training of Brazilian Jiu-Jitsu as a form of reducing aggression for people who are manifesting excessive and uncontrolled aggression in social relations.